Development of a One-Step Multiplex Real-Time PCR Assay for the Detection of Viral Pathogens Associated With the Bovine Respiratory Disease Complex - Zhang, Juan; Wang, Wan; Yang, Mujiao; Lin, Jun; Xue, Fei; Zhu, Yuanmao; Yin, Xin (Frontiers in Veterinary Science, 2022)
Bovine respiratory disease complex (BRDC) occurs widely in cattle farms. The main viral pathogens include bovine viral diarrhea virus (BVDV), Infectious bovine rhinotracheitis virus (IBRV), bovine parainfluenza virus type 3(BPIV3), and bovine respiratory syncytial virus (BRSV), and the newly emerged influenza D virus (IDV). Currently, no sensitive and specific assays were developed for simultaneous detection of these five respiratory disease viruses. In this study, we have developed a one-step multiplex real-time Polymerase Chain Reaction (PCR) capable of sensitively and accurately detecting the five viral pathogens causing BRDC. The established assay could specifically detect targeted viruses without cross-reaction with others. The detection limit was approximately 10 copies/reaction for single real-time PCR and 100 copies/ reaction for multiplex real-time RT-PCR assay, which was equivalent to the cycle threshold (CT) value of ~36 for BVDV, IBRV and BPIV3, ~37 for IDV, ~39 for BRSV. A total of 213 nasal samples from cattle with signs of respiratory tract disease were collected for performance evaluation of the established platform, proving that the method has good specificity and sensitivity. The surveillance data suggested that BVDV and IBRV infection is the dominant cause of BRDC in the herd, whereas the detection rate of IDV, BIPV3, and BRSV in the clinical samples is lower. In summary, the established assay provides technical support for rapid clinical detection of bovine respiratory syndrome viral pathogens to guide the formulation of BRDC prevention and control measures.